How do characteristics of donors and their children influence volume and composition of banked milk? - Pasqua Anna Quitadamo; Giuseppina Palumbo; Alberto Gatta; Liliana Cianti; Massimiliano Copetti; Maria Assunta Gentile; Pierpaolo Cristalli (Hygeia Press di Corridori Marinella, 2018)
When own mother's milk is not available, donor human milk (DHM) is the first choice in preterm infant feeding. Although worldwide strong efforts have been made to implement human milk (HM) donation, there is currently little available research on donors characteristics and their influence on volume and composition of DHM. The present study aimed to evaluate the relationship between social-demographic variables of donating mothers (age, residence, job, number of children), as well as gestational age and birth weight of their babies, and volume and composition of donated HM. The analysis of data revealed a statistically significant impact of maternal age and profession, as well as babies' birth weight and donation duration, on the volume of milk donation, but no effect of donor's place of residence. Gestational age also had an effect on the volume of milk donation, but the effect was not statistically significant (p-value on the verge of significance). Regarding milk composition, gestational age < 29 weeks, low birth weight and overall donation period were statistically correlated to higher protein content. Statistical analysis of other DHM components did not result significant except for carbohydrates, being their content inversely associated with birth weight, with p-value at the margin of significance.